Experts consensus on epidemic prevention and control in radiotherapy centers during the COVID-19 outbreak: Experiences from Sichuan Province - Zhang, Dekang (Clin Transl Radiat Oncol, 2020)
After the outbreak of COVID-19, medical institutions in China and even around the world are facing unprecedented challenges. In order to minimize the adverse impact of this unexpected epidemic on patients who need radiotherapy, the expert group of our radiotherapy center immediately formulated comprehensive emergency plans and prevention and control measures, partitioned the work area, launched online staff training, and optimized the radiotherapy process after the outbreak, which provided a strong guarantee for the safe and orderly operation of our radiotherapy center and kept the infection rate to an extremely low level. We hope our experience could provide reference and suggestions for other medical institutions.